Mixed-Dimensional Assembly Strategy to Construct Reduced Graphene Oxide/Carbon Foams Heterostructures for Microwave Absorption, Anti-Corrosion and Thermal Insulation - Zhan, Beibei; Qu, Yunpeng; Qi, Xiaosi; Ding, Junfei; Shao, Jiao‑jing; Gong, Xiu; Yang, Jing‑Liang; Chen, Yanli; Peng, Qiong; Zhong, Wei; Lv, Hualiang (Nano-Micro Letters, 2024)
Considering the serious electromagnetic wave (EMW) pollution problems and complex application condition, there is a pressing need to amalgamate multiple functionalities within a single substance. However, the effective integration of diverse functions into designed EMW absorption materials still faces the huge challenges. Herein, reduced graphene oxide/carbon foams (RGO/CFs) with two-dimensional/three-dimensional (2D/3D) van der Waals (vdWs) heterostructures were meticulously engineered and synthesized utilizing an efficient methodology involving freeze-drying, immersing absorption, secondary freeze-drying, followed by carbonization treatment. Thanks to their excellent linkage effect of amplified dielectric loss and optimized impedance matching, the designed 2D/3D RGO/CFs vdWs heterostructures demonstrated commendable EMW absorption performances, achieving a broad absorption bandwidth of 6.2 GHz and a reflection loss of − 50.58 dB with the low matching thicknesses. Furthermore, the obtained 2D/3D RGO/CFs vdWs heterostructures also displayed the significant radar stealth properties, good corrosion resistance performances as well as outstanding thermal insulation capabilities, displaying the great potential in complex and variable environments. Accordingly, this work not only demonstrated a straightforward method for fabricating 2D/3D vdWs heterostructures, but also outlined a powerful mixed-dimensional assembly strategy for engineering multifunctional foams for electromagnetic protection, aerospace and other complex conditions. Highlights: 1 Reduced graphene oxide/carbon foams (RGO/CFs) vdWs heterostructures are efficiently fabricated via a simple mixed-dimensional assembly strategy. 2 Linkage effect of optimized impedance matching and enhanced dielectric loss abilities endows the excellent microwave absorption performances of RGO/CFs vdWs heterostructures. 3 Multiple functions such as good corrosion resistance performances and outstanding thermal insulation capabilities can be integrated into RGO/CFs vdWs heterostructures.